The Effect of Giving Salak (Salacca Zalacca) Bark Extract on Liver Function and Histopathological Features of the Liver of Male Wistar White Rats Obesity Model - Arhami, Ade; Djohan, Lina Tantoso; Rajagukguk, Horas (International Journal of Public Health Excellence (IJPHE), 2024)
Nonalcoholic fatty liver disease (NAFLD) Lifestyle factors contribute to fatty liver disease. Physical activity, weight loss, and antioxidant-rich components like Salak herb are used to minimize liver disease. The study examined how Salak bark extract affected liver function in white male Wistar rats, an obesity model, and histopathology. An actual experiment or laboratory experimental design is used in this quantitative research. Four experimental groups of 24 mice were employed. Research data was analyzed with SPSS 25.0. Normality test findings reveal 2-tailed significance of 0.991 > 0.05. The One-Way ANOVA test at a 95% confidence level for the SGOT liver function analysis data showed the same variance, 0.233 (p>0.05) and 0.718 (p>0.05) for the SGPT liver function analysis. Histopathological studies showed snake fruit extract at 300mg/BW scored 3 (Hydropic degeneration), 500mg/BW scored 2 (Parenchymatous degeneration), and 700mg/BW scored 1 (Normal). The phytochemical screening of alkaloids, flavonoids, saponins, tannins, and glycosides demonstrated that Salak bark extract's secondary metabolite concentration contains antioxidant-effective active components. The study demonstrated no inflammation, cell improvement, necrosis, or fat at 700 mg/BW.